2022
DOI: 10.1530/rep-21-0308
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory response elicited by Ureaplasma parvum colonization in human cervical epithelial, stromal, and immune cells

Abstract: Ureaplasma parvum is a commensal bacterium in the female reproductive tract but has been associated with pregnancy complications such as preterm prelabor rupture of membranes and preterm birth (PTB). However, the pathologic effects of U. parvum in the cervix, that prevents ascending infections during pregnancy, are still poorly understood. To determine the impact of U. parvum on the cervix, ectocervical (ecto) and endocervical (endo) epithelial and stromal cells were incubated with U. parvum. Macrophages were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 62 publications
3
29
0
Order By: Relevance
“…This was also supported by various in vitro and in vivo studies showing a dose-dependent increase in inflammation and PTB rate with higher doses of Ureaplasma spp. infections ( Glaser et al, 2017 , 2018 ; Motomura et al, 2020 ; Tantengco et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was also supported by various in vitro and in vivo studies showing a dose-dependent increase in inflammation and PTB rate with higher doses of Ureaplasma spp. infections ( Glaser et al, 2017 , 2018 ; Motomura et al, 2020 ; Tantengco et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, this conclusion may depend on their load, location and polymicrobial presence. Our own in vitro studies have shown that poor immunogenicity by these microbes in human fetal membranes as well as in the cervix ( Noda-Nicolau et al, 2016 ; Tantengco et al, 2021 , 2022 ). These results suggest that the association between the genital mycoplasmas and adverse pregnancy outcomes might not be strong enough to warrant universal antimicrobial intervention.…”
Section: Discussionmentioning
confidence: 99%
“…58 Most of our knowledge regarding the pathologic effects of bacterial infection in the cervix during pregnancy is based on in vivo animal and in vitro cell culture studies. 3,32,36,46 However, some findings from animal models may not apply to humans due to the inherent anatomical and physiological differences between humans and animal models, as well as the multifetal pregnancies in many of the routinely used models (e.g., mice and rats). Conversely, in vitro 2D cell culture studies also have limitations due to For all groups, n ≥ 3 pregnant mice.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the mechanistic and pathophysiologic effects of bacterial infections in the cervix during pregnancy are limited due to the difficulty of obtaining cervical samples 30 . The majority of the studies on the cellular damage caused by cervical infections were conducted using in vitro monocultures and animal models, including CD‐1 mice 31–36 . Previous studies have used CD‐1 mice in studying preterm cervical ripening and the role of LPS‐induced inflammation and Escherichia coli infection in PTB 37–39 .…”
Section: Introductionmentioning
confidence: 99%
“…The cells were then centrifuged at 1,000 rpm for 5 min. THP-1 monocytes were seeded in a 48-well plate (50,000 cells per well), and they were differentiated to THP-1 macrophages by incubating them in a culture medium containing 100 mM phorbol 12-myristate 13-acetate for three days at 37°C and 5% CO 2 environment, and grown to 80% confluency as described previously ( Tantengco et al, 2021a ).…”
Section: Methodsmentioning
confidence: 99%